ANALISIS KEUNTUNGAN USAHA â€œCAPTIKUSâ€ DI DESA POOPO BARAT KECAMATAN PASSI TIMUR, KABUPATEN BOLAANG MONGONDOW (Profit Analysis of "Captikus" Business in West Poopo Village, East Passi District, Bolaang Mongondow Regency Lisa G. Tewal, Gene H. M. Kapantow, dan Yolanda P. I. Rori) - Lisa G. Tewal; Gene H. M. Kapantow; Yolanda P. I. Rori (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
This study aims to analyze the profits of â€œCaptikusâ€ (local alcoholic drinks) business in Poopo Village, East Passi District. This research was conducted for three months, from October to December 2020. The sampling method used was purposive sampling, to select 20 captikus producer as respondents. The data used in this study are primary data and secondary data. Primary data was obtained by conducting direct interviews with producers using a list of questions that had been prepared. Secondary data were obtained from agencies involved in this study. The data analysis used in this research is business profit analysis.The results showed that the â€œcaptikusâ€ producers in West Poopo Village, East Passi District, on average got a profit of IDR 2,332,379, - / month. The R / C value for the â€œcaptikusâ€ business in this village was 1,96. This showed that the â€œcaptikusâ€ business in Poopo Barat Village, East Passi District can continue to be developed because it will provide adequate benefits for â€œcaptikusâ€ producers.